2001
DOI: 10.1590/s0074-02762001000600020
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a new tablet formulation based on Bacillus thuringiensis sorovar. israelensis for larvicidal control of Aedes aegypti

Abstract: The effect of sunlight on the efficacy and persistence of an experimental tablet formulation based on Bacillus thuringiensis sorovar. israelensis (C4P1) was evaluated against Aedes aegypti larvae under simulated field conditions. The initial mortality ranged from 93 to 100%, and the residual activity (≥ 70% mortality) recorded in containers exposed to sunlight or shade were, respectively, 13-35 days and 40-54 days. The results suggest that C4P1 can provide long-term larvicidal effect and operational advantages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 4 publications
1
15
0
1
Order By: Relevance
“…Extrinsic environmental characteristics also influence treatment efficacy, particularly sunlight which degrades the protoxins (Burke et al 1983;Becker et al 1992;de Melo-Santos et al 2001). For example, three times more Bti is required for 90% mortality of Aedes aegypti (Linnaeus) at 48 h in sunlight compared with shade (Becker et al 1992).…”
Section: Microbial Insecticidesmentioning
confidence: 99%
“…Extrinsic environmental characteristics also influence treatment efficacy, particularly sunlight which degrades the protoxins (Burke et al 1983;Becker et al 1992;de Melo-Santos et al 2001). For example, three times more Bti is required for 90% mortality of Aedes aegypti (Linnaeus) at 48 h in sunlight compared with shade (Becker et al 1992).…”
Section: Microbial Insecticidesmentioning
confidence: 99%
“…The assessment of some vector control strategies has been undertaken in the Philippines, including the use of the microbial agent Bacillus thuringiensis israelensis in water containers (de Melo-Santos et al, 2001;Mahilum et al, 2005), and insecticide-treated curtains inside houses (Madarieta et al, 1999). A multifaceted vector control approach, that includes environmental management and chemical and biological methods, has also been suggested (Su, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The last few decades experienced the use of insecticides of biological origin against the larvae of Aedes aegypti (Cheng et al 2003;Harvae and Kamath 2004;Koodalingam et al 2009;Kumar et al 2010;Oliveira et al 2010). In recent times, there has been major concern for the promotion of plant-based insecticides including microbial (Melo-Santos et al 2001;Wang and Jaal 2005;Pontes et al 2010) and insect growth regulators (Sihunincha et al 2005;Vythilingam et al 2005). However, recent reports have shown that the use of microbes like Bacillus sphaericus as a potent biolarvicide in India is limited due to the development of resistance towards these compounds in the laboratory and in the field conditions (Poopathi and Tyagi 2002;Singh and Prakash 2009).…”
Section: Discussionmentioning
confidence: 99%